The stable Cr isotopic compositions of chondrites and silicate planetary reservoirs. (15th June 2016) - Schoenberg, Ronny; Merdian, Alexandra; Holmden, Chris; Kleinhanns, Ilka C.; Haßler, Kathrin; Wille, Martin; Reitter, Elmar
Abstract: The depletion of chromium in Earth's mantle (∼2700 ppm) in comparison to chondrites (∼4400 ppm) indicates significant incorporation of chromium into the core during our planet's metal–silicate differentiation, assuming that there was no significant escape of the moderately volatile element chromium during the accretionary phase of Earth. Stable Cr isotope compositions – expressed as the ‰-difference in 53 Cr/ 52 Cr from the terrestrial reference material SRM979 ( δ 53/52 CrSRM979 values) – of planetary silicate reservoirs might thus yield information about the conditions of planetary metal segregation processes when compared to chondrites. The stable Cr isotopic compositions of 7 carbonaceous chondrites, 11 ordinary chondrites, 5 HED achondrites and 2 martian meteorites determined by a double spike MC-ICP-MS method are within uncertainties indistinguishable from each other and from the previously determined δ 53/52 CrSRM979 value of −0.124 ± 0.101‰ for the igneous silicate Earth. Extensive quality tests support the accuracy of the stable Cr isotope determinations of various meteorites and terrestrial silicates reported here. The uniformity in stable Cr isotope compositions of samples from planetary silicate mantles and undifferentiated meteorites indicates that metal–silicate differentiation of Earth, Mars and the HED parent body did not cause measurable stable Cr isotope fractionation between these two reservoirs. Our results also imply that the accretionary disc, at least in the inner solar system, was homogeneous in its stable Cr isotopic composition and that potential volatility loss of chromium during accretion of the terrestrial planets was not accompanied by measurable stable isotopic fractionation. Small but reproducible variations in δ 53/52 CrSRM979 values of terrestrial magmatic rocks point to natural stable Cr isotope variations within Earth's silicate reservoirs. Further and more detailed studies are required to investigate whether silicate differentiation processes, such as partial mantle melting and crystal fractionation, can cause stable Cr isotopic fractionation on Earth and other planetary bodies.